Parenthesis ebook - Durand, Élodie (Parenthesis., 2021)
A triumph of graphic memoir, Parenthesis narrates the author's experience with tumor-related epilepsy—losing herself, and finding herself again. Julie is barely out of her teens when a tumor begins pressing on her brain, ushering in a new world of seizures, memory gaps, and loss of self. Suddenly, the sentence of her normal life has been interrupted by the opening of a parenthesis that may never close. Based on the real experiences of cartoonist Élodie Durand, Parenthesis is a gripping testament of struggle, fragility, acceptance, and transformation which was deservedly awarded the Revelation Prize of the Angoulême International Comics Festival.